Islamic banking and sharfah scholars in Nigeria (2016)
Compliance with Shari'ah rules is compulsory for all Islamic banks; and such compliance is monitored by Shari'ah scholars. Therefore, this article examines and gauges the level of understanding of Nigerian Shari'ah scholars (the custodians of Shari'ah rules in the country) and their perceptions of the Islamic banking and its rules particularly interest (riba). The survey method involving the use of purposive sampling was adopted to administer 1,040 copies of a questionnaire sent to Nigerian Shari'ah scholars, though some key people were also interviewed. The questionnaire, which contains 19 items, was designed to elicit information from them on issues such as their understanding of riba, its uses in the Qur'an, Islamic banking products, collateral security and promotion (promos). Our findings revealed that there were more respondents (917) who considered usury to be forbidden than those who considered (871) interest to be forbidden. A large number of Shari'ah scholars (93.6%) confused interest with usury which suggests that both interest and usury refer to riba. Some believed that riba (48.6%) only refers to usury, while most of the respondents (74.1%) opined that all forms of interest are prohibited. About 73.7%, 86.3%, and 27.6% of the respondents believed rahn (collateral security), innovating interest-free financial products and patronising conventional banks respectively were allowed. The Shari'ah scholars surveyed (64.7%) believed that conventional financial products can be made Shari’ah-compliant, banks can operate successively without interest (89%), and they (70.3%) were of the views that promotions done by the conventional banks are against the teachings of Islam considering the source of the funds used in their promotions which contains the accrued interest income and lack of fairness in the distributions of the promotions. Seminars, workshops, and conferences can be organized for the scholars with a view to training them in the areas of Islamic banking and finance. Collaboration can be established between the Nigerian Shari'ah scholars and the Shari'ah scholars from the Middle East so that the former can benefit from the wealth of experience of the latter in the areas of Islamic banking and finance.